Consumer Protection in the Digital Economy Era: Tiktok Shop Case Study - Maharany, Sylvana Aninditha (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The development of technology has inevitably caused a shift where now society has entered the era of the digital economy where both individuals and organizations use technology in carrying out their economic activities. Indonesia is seen as having great potential in the digital economy which then causes the government to make it a priority issue. This in turn will lead to a significant increase in the value of the digital economy which is estimated to reach US$ 330 billion by 2025. This study aims to analyze consumer protection in the digital economy era: a case study of Tiktok Shop. This study uses a normative approach that focuses on descriptive analysis and discussion of the digital economy phenomenon in Indonesia, especially Tiktok Shop. The results of this writing explain that the emergence of TikTok Shop is seen as having presented new challenges to the existing regulatory framework and law enforcement mechanisms, especially related to consumer protection. The closure of TikTok Shop was essentially due to TikTok Shop not having a trading license as an e-commerce platform according to regulations in Indonesia. Therefore, it is important for TikTok Shop to demonstrate compliance with applicable regulations in Indonesia, especially regarding consumer protection. Self-regulation can effectively provide legal protection and customer trust in online purchases.